2021
DOI: 10.3390/ijms222011179
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived PCSK9 Is Associated with LDL Metabolism and Modulates Atherothrombotic Mechanisms in Coronary Artery Disease

Abstract: Platelets play a significant role in atherothrombosis. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is critically involved in the regulation of LDL metabolism and interacts with platelet function. The effect of PCSK9 in platelet function is poorly understood. The authors of this article sought to characterize platelets as a major source of PCSK9 and PCSK9’s role in atherothrombosis. In a large cohort of patients with coronary artery disease (CAD), platelet count, platelet reactivity, and platelet-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…Accordingly, collective studies have demonstrated that PCSK9 directly promotes atherosclerosis by being involved in atherosclerotic inflammation [16][17][18]. Furthermore, recent studies suggested a novel role for PCSK9 in promoting atherosclerosis through platelet activation, a key role during atherogenesis and in atherothrombosis-induced MI [35,36,[62][63][64]. Notably, several clinical studies have demonstrated the antiplatelet effects of PCSK9 in patients with hypercholesterolemia and found it to be an effective and safe strategy for treating patients with uncontrolled hyperlipidemia and coronary artery disease [65,66].…”
Section: Pcsk9 and MImentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, collective studies have demonstrated that PCSK9 directly promotes atherosclerosis by being involved in atherosclerotic inflammation [16][17][18]. Furthermore, recent studies suggested a novel role for PCSK9 in promoting atherosclerosis through platelet activation, a key role during atherogenesis and in atherothrombosis-induced MI [35,36,[62][63][64]. Notably, several clinical studies have demonstrated the antiplatelet effects of PCSK9 in patients with hypercholesterolemia and found it to be an effective and safe strategy for treating patients with uncontrolled hyperlipidemia and coronary artery disease [65,66].…”
Section: Pcsk9 and MImentioning
confidence: 99%
“…Another interesting in vitro study was conducted by Petersen et al, who demonstrated that PCSK9 was stored and released by platelets in the presence of LDL [64]. The PCSK9-derived platelet was found to promote platelet aggregation, thrombus formation, monocyte migration, and monocyte differentiation into foam cells, all of which contributed to the occurrence of atherosclerosis progression-induced coronary artery disease [64]. Next, experimental studies were performed in an attempt to find a potential mechanism underlying PCSK9 and platelet activation in the progression of atherosclerosis.…”
Section: Pcsk9 Promotes Platelet Activationmentioning
confidence: 99%
“…Furthermore, it has recently been described for the first time that platelets also express PCSK9 upon activation in the presence of LDL, and that its secretion by platelets further contributes to their aggregation and thrombus formation. In addition, this promotes monocyte differentiation into macrophages/foam cells, also contributing to atherogenesis [ 65 ].…”
Section: Impact Of Pcsk9 On Platelets and Blood Coagulationmentioning
confidence: 99%
“…The effect of PCSK9 inhibitors on platelet function has been extensively studied. Monoclonal antibodies against PCSK9 reduce platelet activation and platelet–dependent immunothrombosis [ 65 , 90 ]. Inclisiran, a small interfering RNA-based PSCK9, has not shown any effect on platelets thus far [ 91 ].…”
Section: The Effect Of Pcsk9 Inhibitors On Platelet Function and Thro...mentioning
confidence: 99%
“…In the presence of PCSK9 antibodies platelet aggregation was significantly attenuated. As a result, in presence of PSCK9 antibodies, platelet-dependent thrombus formations significantly reduced [68]. Many studies indicate that statins [69] and PCSK9 monoclonal antibodies [70] have an effect on the hemostatic system.…”
Section: Pcsk9 and Platelets' Functionmentioning
confidence: 99%